PENGOLAHAN SAMPAH ORGANIK DAN ANORGANIK DESA KARANGJATI - Nugroho, Aditya; Fauzy, Ahmad Abdurrohman; Salsabila, Arina A’ina; Adnan, Cahya Ratna Sabilla Riani; Satia, Chenny Cadi; Hidayahtulloh, Maulid Agil; Azami, Muhammad Rafi; Nugraha, Oka Dewa; Yasir, Roykhan Khilbi; Abdur, Sylva Rafflesia; Kholis, Zenith Tsabitha; Al-Afik, Al-Afik (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2026)
Household waste management in Karangjati Village, Wonosegoro District, Boyolali Regency still faces serious problems in the form of open burning and dumping of waste into rivers due to the lack of an organized waste management system. This condition has the potential to cause environmental pollution and health hazards to the community, even though the village has considerable potential for organic waste from household and agricultural activities that can be used for composting. This community service activity through the University of Muhammadiyah Yogyakarta's Community Service Program (KKN) aims to increase knowledge and skills, as well as encourage changes in community attitudes and behavior in organic waste management based on appropriate technology, while also initiating integrated waste management through the concept of a waste bank. The implementation method uses an educational and participatory approach, which includes observation and coordination with village officials, socialization of 3R-based waste management, training in making simple composters from two used gallons, and the initial initiation of a waste bank. The results of the activity show a fairly high level of community participation in the socialization and composting practice stages. The composter, which has been in operation since January 30, 2026, is used for waste types that are predominantly food scraps and garden waste, indicating an initial change in behavior in the sorting and processing of organic waste. Qualitatively, residents and health cadres stated that some organic waste is no longer burned or disposed of indiscriminately, but is instead transferred to composters, although quantitative measurements of the reduction in waste volume are still in the observation stage. This program shows that the application of simple technology based on local potential is effective as a first step in community empowerment, but sustainability requires continued assistance, strengthening of village institutions, and a more structured monitoring system.